Perspectivas para a formação docente diante do prisma da filosofia pósmetafísica de Habermas - Melo, Elvis Francis Furquim de (2009)
The research consists in a bibliographic approach concerning the exercise of the critical hermeneutic in the theory of communicative action in Jürgen Habermas. The proposal of interpretive analysis can reconstruct the assumptions of pedagogy and the formation in the tradition of the history. The post-metaphysical thinking has the potential for multiple experience of the decentralized reason that rethinks the model of the consciousness. Your emancipatory project considers the critical power of the reason in the perspective of the potential of communicative language. It is in the own language, before being ideology, before exercising the power, before the domination, first of all, it has cognitive and intellectual power. In this linguistic ambient presents as cognitive activity the structural aspect, a speech of free conditions, not against the speech of the other, not to dominate, but to be understood. In this communicative theory, the challenge is to restore the hidden thought to the objectivist sciences, trying to reconnect the dimension of philosophy and education. It is with this expansion of restoration of the expectations of the cultural assumptions, social, human forgotten by the tradition of the history, that open the intention to contribute to the education, enabling a plural language that can attend the needs of the debate in the scope of teacher formation of our time.